ANALYSIS OF THE ACRONYM WRITING ON THE PRESIDENTIAL ELECTION CAMPAIGN OF THE 2019-2024 PERIOD - Abdul Haris Faisal (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
Abstract This study discusses the renewal carried out by the acronym needed in campaign campaigns for presidential and vice-presidential candidates. To find out the errors related to the acronym that existed in the campaign viewer, this study used a qualitative descriptive method. The results of this study indicate the facts that appear on promotional devices. Mistakes in using this acronym are needed in campaign campaigns for the election of presidential and vice-presidential candidates. The error was issued by a selection error that was too imposing. Keywords: acronyms, errors, and campaign props